Tea, addiction and late Victorian narratives of degeneration, c. 1860-1900 - Miller, Ian (Routledge handbook of intoxicants and intoxication, 2023)
Historians of tea have typically focused on tea in colonial economies or how Victorian tea parties functioned as a marker of middle-class civility. There have been far less attention to problematic aspects of tea drinking: excessive consumption, historical reliance on tea as a dietary staple, addiction and ‘intoxication’. Such issues are glossed over, if mentioned at all, in the various popular history books on tea. This essay traces concern over tea drinking with a focus on the nineteenth century, a period when tea began to be consumed across the social spectrum and when many working-class mothers came to rely upon it as a dietary staple. This raised considerable concern among doctors and the middle classes who saw ‘excessive tea drinking’ as decadent, unhealthy and morally problematic. Some doctors considered tea as dangerous as opium and identified it as innutritious and potentially damaging to physical and mental health. Late nineteenth-century Britain and Ireland saw a moral panic about ‘excessive tea drinking’ which, once addiction had set in, was thought to trigger severe mental illness such as hysteria. In Ireland, an 1894 government inquiry concluded that excessive tea drinking, with its mental stimulation and exhilaration, was the leading cause of rising asylum admissions across the country. Broadly, corresponding concerns arose in America. Throughout the late nineteenth century, working-class mothers were accused of over-consuming strong concoctions of tea (with white bread) at the expense of more nutritious food items. These perspectives missed the point that over-reliance on tea was a symptom of working-class poverty and a means of allocating more nutritious food items to other household members. However, they highlight the class and gender-based connotations underpinning the simple act of drinking a cup of tea and how these could cause tea drinking to be viewed negatively as addictive, transgressive and pathological.